AgInS2 / ZnS quantum dot with high fluorescence luminous efficiency, preparation method of AgInS2 / ZnS quantum dot and application of AgInS2 / ZnS quantum dot in white light emitting diode
By extending the zinc ion exchange process and supplementing with ZnS shell coating, the problem of low photoluminescence characteristics of AgInS2-based quantum dots in the short wavelength range is solved, which significantly improves the green luminescence efficiency and improves the color development performance of white light emitting diodes.
Patent Information
- Application Number
- CN202510418780.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-06-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing AgInS2-based quantum dots have low photoluminescence characteristics in the short wavelength range, which limits the improvement of color development performance of white light emitting diodes.
By extending the zinc ion exchange process and supplementing with ZnS shell coating, the generation of lattice defects in the AgInS2 core quantum dots is reduced, the exciton binding energy is improved and the phonon coupling is reduced, thereby enhancing the luminous efficiency of green AgInS2/ZnS quantum dots.
The green luminescence efficiency of AgInS2/ZnS quantum dots is significantly improved, the color development performance of white light emitting diodes prepared based on this quantum dots is improved, and a strategy is provided for the emission wavelength adjustment and luminescence efficiency enhancement of other I-III-VI semiconductor nanocrystals.
Smart Images

Figure CN120192770A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor materials, and particularly to an AgInS2 / ZnS quantum dot with high fluorescence emission efficiency, a preparation method thereof, and an application thereof in a white light emitting diode. Background Art
[0002] I-III-VI semiconductor quantum dots (QDs), such as CuInS2, CuInSe2, and AgInS2, have received extensive attention as potential alternatives to commonly used lead-based and cadmium-based quantum dots. These chalcogenide semiconductor quantum dots have shown extraordinary application potential in fields such as solar cells, photocatalysis, photoelectrochemical sensors, and light emitting diodes due to their low toxicity, direct bandgap, and high extinction coefficient in the visible to near-infrared region.
[0003] AgInS2 quantum dots have a relatively wide bandgap range (1.87 - 2.03 eV) and exhibit many unique properties in absorption and photoluminescence (PL) spectra. Most studies on AgInS2 materials focus on the controllable synthesis of high-performance quantum dots and their application in bioimaging, catalysis, sensing, and light emitting devices. Among them, by utilizing the inherent broadband emission characteristics of AgInS2-based quantum dots in white light emitting diodes (WLEDs), the color rendering index (CRI) can be significantly improved while reducing costs, making it a promising alternative to traditional phosphor-based WLEDs. By adjusting the silver / indium ratio, pure AgInS2 core quantum dots can easily achieve emission wavelengths from approximately 600 nm to 800 nm. Coating the AgInS2 core with a wider bandgap semiconductor (such as ZnS) can further extend the emission wavelength to shorter wavelengths and improve the photoluminescence quantum yield (PL QY) of the quantum dots. A large number of studies have shown that coating with a ZnS shell is an effective strategy to reduce surface defects of quantum dots, thereby improving the PL QY and stability of AgInS2-based quantum dots. Optimized high-quality AgInS2-based core / shell quantum dots can achieve emission wavelengths in the range of 500 nm to 700 nm, and the PL QY in the yellow-red emission region is as high as 60% - 90%. The luminance efficiency of green-emitting AgInS2-based quantum dots is still relatively low, which limits the further improvement of the color rendering performance of AgInS2-based WLEDs.
[0004] At present, expanding the bandgap of AgInS2 quantum dots through zinc ion exchange to achieve green emission is the most common and effective strategy. Zinc ion exchange can be achieved by introducing zinc precursors during the AgInS2 nucleation process or increasing the temperature of the ZnS shell to promote the incorporation of zinc ions into the AgInS2 lattice. Currently, research on the photoluminescence properties of AgInS2-based quantum dots mainly focuses on their long-wavelength characteristics, while less attention is paid to the green emission in the short-wavelength range, especially the low luminescence efficiency in the green emission characteristics. In addition, WLED devices based on AgInS2-based quantum dots still have room for further improvement in various color rendering performances. Summary of the Invention
[0005] The object of the present invention is to provide a kind of AgInS2 / ZnS quantum dots with high fluorescence emission efficiency, its preparation method and application in white light emitting diodes, so as to solve the technical problem of improving the photoluminescence properties of AgInS2-based quantum dots in the short-wavelength range.
[0006] In order to achieve the above-mentioned invention object, the present invention provides the following technical solutions: The present invention provides a preparation method of AgInS2 / ZnS quantum dots with high fluorescence emission efficiency, comprising the following steps: 1) Mix silver nitrate, indium chloride, oleic acid, dodecanethiol and octadecene and react, and obtain a mixture after heating; 2) Rapidly add a sulfur precursor to the mixture and react at a certain temperature to obtain AgInS2 core quantum dots; 3) Add a zinc-sulfur precursor mixture to the AgInS2 core quantum dots for reaction to form a ZnS shell; then add the same amount of zinc-sulfur precursor mixture again for a secondary reaction to obtain AgInS2 / ZnS quantum dots with high fluorescence emission efficiency.
[0007] Further, the molar ratio of silver nitrate to indium chloride is 0.02~0.4:0.4; The dosage ratio of silver nitrate, oleic acid, dodecanethiol and octadecene is 0.02~0.4 mmol:0.5~0.8 mmol:2~4 mmol:5~15 mL.
[0008] Further, in the step 1), the reaction temperature is 80~90 °C, the reaction time is 20~30 min; the heating temperature is 120~140 °C.
[0009] Further, the sulfur precursor is prepared by dissolving sulfur powder in oleylamine, and the dosage ratio of sulfur powder to oleylamine is 0.2~0.4 mmol:4 mL.
[0010] Further, in step 2), the reaction temperature is 100~120 °C and the reaction time is 10~20 min.
[0011] Further, the zinc sulfide precursor mixture is obtained by dissolving zinc stearate and sulfur powder in a mixed solvent of trioctyl phosphate and octadecene, and the dosage ratio of zinc stearate, sulfur powder, trioctyl phosphate and octadecene is 0.4~0.8 mmol: 0.3 mmol: 2 mL: 2 mL.
[0012] Further, in step 3), the reaction temperature is 170~190 °C and the reaction time is 0.5~2 h.
[0013] Further, in step 3), the temperature of the secondary reaction is 200~220 °C and the time of the secondary reaction is 0.5~2 h.
[0014] The present invention also provides an AgInS2 / ZnS quantum dot with high fluorescence emission efficiency.
[0015] The present invention also provides an application of an AgInS2 / ZnS quantum dot with high fluorescence emission efficiency in a white light emitting diode.
[0016] Advantages of the present invention: By prolonging the zinc ion exchange process and supplemented with ZnS shell coating, the present invention can reduce the generation of lattice defects in the AgInS2 core quantum dots caused by rapid ion exchange. The method of the present invention improves the exciton binding energy, reduces the phonon coupling, effectively enhances the luminescence efficiency of the green AgInS2 / ZnS quantum dots, and further improves the color rendering performance of the white light emitting diode obtained based on the AgInS2 / ZnS quantum dots. The present invention provides a potential strategy for adjusting the emission wavelength and enhancing the luminescence efficiency in other I-III-VI semiconductor nanocrystals. Description of the drawings
[0017] Figure 1 Absorption and PL spectra of AgInS2 quantum dots with different silver / indium ratios prepared for the examples. (b) Schematic diagram of interband and intraband of AgInS2 quantum dots.
[0018] Figure 2 Absorption and photoluminescence (PL) spectra of AgInS2:Zn / ZnS quantum dots at different reaction times prepared for the examples and comparative examples; (b) Absorption and PL spectra of AgInS2 / ZnS quantum dots at different reaction times; (c) Relationship diagram of the PL peak value and full width at half maximum (FWHM) of AgInS2:Zn / ZnS (upper) and AgInS2 / ZnS (lower) quantum dots varying with the reaction time. The inset is a photo of the quantum dot solution taken under 365 nm ultraviolet light.
[0019] Figure 3 TEM images of (a) AgInS2 cores prepared in Example 1, (b) AgInS2:Zn prepared in Comparative Example 1, (c) AgInS2:Zn / ZnS prepared in Comparative Example 1, and (d) AgInS2 / ZnS quantum dots prepared in Example 1. The inset is a histogram of the particle size distribution.
[0020] Figure 4 Emission spectra of quantum dots with different emission wavelengths prepared in the examples of the present invention. The inset is a photograph of the quantum dot solution taken under 365 nm ultraviolet light.
[0021] Figure 5 EL spectra of (a) the first WLED and the second WLED prepared in the application example. (c) CRI Ra and CCT of the device at different driving currents (from 10 mA to 100 mA). (d) Light efficiency (LE) graph of the device from 0 to 10 hours.
[0022] Figure 6 Electroluminescence (EL) spectra of (a) the first WLED; (b) the second WLED at different currents (from 10 to 100 mA).
[0023] Figure 7 Schematic diagram of the synthesis routes of the quantum dots of the examples and comparative examples of the present invention. Detailed implementation manners
[0024] The present invention provides a method for preparing AgInS2 / ZnS quantum dots with high fluorescence emission efficiency, comprising the following steps: 1) Mix silver nitrate, indium chloride, oleic acid, dodecanethiol and octadecene and react, and obtain a mixture after heating; 2) Rapidly add a sulfur precursor to the mixture and react at a certain temperature to obtain AgInS2 core quantum dots; 3) Add a zinc-sulfur precursor mixture to the AgInS2 core quantum dots to react to form a ZnS shell; then add the same amount of zinc-sulfur precursor mixture again for a secondary reaction to obtain AgInS2 / ZnS quantum dots with high fluorescence emission efficiency.
[0025] In the present invention, the molar ratio of silver nitrate to indium chloride is 0.02 - 0.4:0.4, preferably 0.05 - 0.2:0.4, and more preferably 0.08 - 0.2:0.4.
[0026] In the present invention, the dosage ratio of silver nitrate, oleic acid, dodecanethiol and octadecene is 0.02 - 0.4 mmol: 0.5 - 0.8 mmol: 2 - 4 mmol: 5 - 15 mL, preferably 0.05 - 0.4 mmol: 0.5 - 0.7 mmol: 2 - 3 mmol: 5 - 10 mL, and more preferably 0.08 - 0.2 mmol: 0.6 mmol: 3 mmol: 8 mL.
[0027] In the present invention, in step 1), the reaction temperature is 80 - 90 °C, preferably 85 °C; the reaction time is 20 - 30 min, preferably 30 min; the temperature for heating up is 120 - 140 °C, preferably 130 °C.
[0028] In the present invention, the sulfur precursor is prepared by dissolving sulfur powder in oleylamine, and the dosage ratio of sulfur powder and oleylamine is 0.2 - 0.4 mmol: 4 mL, preferably 0.3 mmol: 4 mL. In the present invention, sulfur powder is preferably dissolved in oleylamine at 120 °C.
[0029] In the present invention, in step 2), the reaction temperature is 100 - 120 °C, preferably 110 °C; the reaction time is 10 - 20 min, preferably 15 min.
[0030] In the present invention, after the reaction in step 2) ends, the reaction product is purified. The purification reagents are n - hexane and ethanol, and the number of purification times is 2 - 5 times, preferably 3 times. The purified quantum dots are the AgInS2 core quantum dots, and the purified quantum dots are redispersed in n - hexane for subsequent characterization and experiments.
[0031] In the present invention, the zinc - sulfur precursor mixture is obtained by dissolving zinc stearate and sulfur powder in a mixed solvent of tri - octyl phosphate and octadecene. The dosage ratio of zinc stearate, sulfur powder, tri - octyl phosphate and octadecene is 0.4 - 0.8 mmol: 0.3 mmol: 2 mL: 2 mL, preferably 0.6 mmol: 0.3 mmol: 2 mL: 2 mL. In the present invention, zinc stearate and sulfur powder are preferably dissolved in the mixed solvent of tri - octyl phosphate and octadecene at 120 °C.
[0032] In the present invention, in step 3), the reaction temperature is 170 - 190 °C, preferably 180 °C; the reaction time is 0.5 - 2 h, preferably 1 h.
[0033] In the present invention, in step 3), the temperature of the secondary reaction is 200 - 220 °C, preferably 210 °C; the time of the secondary reaction is 0.5 - 2 h, preferably 1 h. The purpose of the secondary reaction in the present invention is to further grow the ZnS shell layer.
[0034] In the present invention, in step 3), after the secondary reaction is completed, the reaction product is purified. The purification reagents are n-hexane and ethanol, and the number of purification times is 2 to 5 times, preferably 3 times. The purified quantum dots are vacuum dried into a powder for the preparation of white light-emitting diodes.
[0035] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0036] Example 1
[0037] 1) 0.05 mmol of silver nitrate (AgNO3), 0.4 mmol of indium chloride hydrate (InCl3·4H2O), 0.6 mmol of oleic acid (OA), 3 mmol of dodecanethiol (DDT), and 8 mL of 1-octadecene (1-ODE) are mixed in a 50 mL three-necked flask. The mixture is heated to 80 °C and evacuated for 30 minutes. Then, the temperature is raised to 130 °C under a nitrogen atmosphere to completely dissolve AgNO3.
[0038] 2) Subsequently, the temperature is lowered to 110 °C, evacuated for 2 hours, and filled with nitrogen. The sulfur precursor (0.3 mmol of sulfur powder dissolved in 4 mL of oleylamine at 120 °C) is rapidly injected into the above mixture for reaction. The reaction is maintained at 110 °C for 15 minutes to promote the growth of AgInS2 core quantum dots. The obtained AgInS2 quantum dots are purified three times using n-hexane and ethanol to obtain AgInS2 core quantum dots with an emission wavelength of 624 nm.
[0039] 3) The zinc-sulfur precursor mixture (at 120 °C, 0.6 mmol of zinc stearate Zn(St)2 and 0.3 mmol of sulfur powder are dissolved in 2 mL of trioctyl phosphate (TOP) and 2 mL of 1-octadecene (ODE)) is injected into the flask containing the above AgInS2 core quantum dots. Subsequently, the reaction temperature is rapidly raised to 180 °C and maintained for 1 hour to form a ZnS shell. Then, the same amount of zinc-sulfur precursor mixture is injected again, and the temperature is raised to 210 °C and maintained for 1 hour to further grow the ZnS shell. The obtained quantum dots are purified three times using n-hexane and ethanol. The purified quantum dots are stored in the form of a n-hexane solution for characterization. Some of the purified quantum dots are vacuum dried into a powder, which is the green-emitting AgInS2 / ZnS quantum dots with an emission wavelength of 524 nm.
[0040] Example 2
[0041] Same as Example 1, except that: 0.08 mmol of silver nitrate (AgNO3) and 0.4 mmol of indium chloride hydrate (InCl3·4H2O) were used, and the emission wavelength of the AgInS2 core quantum dots was 643 nm; the obtained yellow-emitting AgInS2 / ZnS quantum dots had an emission wavelength of 564 nm.
[0042] Example 3
[0043] Same as Example 1, except that: 0.2 mmol of silver nitrate (AgNO3) and 0.4 mmol of indium chloride hydrate (InCl3·4H2O) were used, and the emission wavelength of the AgInS2 core quantum dots was 715 nm; the obtained orange-emitting AgInS2 / ZnS quantum dots had an emission wavelength of 599 nm.
[0044] Example 4
[0045] Same as Example 1, except that: 0.4 mmol of silver nitrate (AgNO3) and 0.4 mmol of indium chloride hydrate (InCl3·4H2O) were used, and the emission wavelength of the AgInS2 core quantum dots was 795 nm; the obtained red-emitting AgInS2 / ZnS quantum dots had an emission wavelength of 632 nm.
[0046] Example 5
[0047] Same as Example 1, except that: 0.02 mmol of silver nitrate (AgNO3) and 0.4 mmol of indium chloride hydrate (InCl3·4H2O) were used, and the emission wavelength of the AgInS2 core quantum dots was 600 nm; the obtained green-emitting AgInS2 / ZnS quantum dots had an emission wavelength of 520 nm. However, due to the inherent defects of the AgInS2 core quantum dots at this ratio, the fluorescence emission efficiency of the final quantum dots was relatively low.
[0048] Example 6
[0049] 1) 0.05 mmol of silver nitrate (AgNO3), 0.4 mmol of indium chloride hydrate (InCl3·4H2O), 0.8 mmol of oleic acid (OA), 3 mmol of dodecanethiol (DDT), and 10 mL of 1-octadecene (1-ODE) were mixed in a 50 mL three-necked flask. The mixture was heated to 90 °C and evacuated for 30 minutes. Then the temperature was raised to 140 °C under a nitrogen atmosphere to completely dissolve AgNO3.
[0050] 2) Subsequently, the temperature was lowered to 105 °C, and vacuum was applied for 2 hours, followed by nitrogen filling. The sulfur precursor (0.3 mmol of sulfur powder dissolved in 4 mL of oleylamine at 120 °C) was rapidly injected into the above mixture for reaction, and the reaction was maintained at 105 °C for 15 minutes to promote the growth of AgInS2 core quantum dots. The obtained AgInS2 quantum dots were purified three times using n-hexane and ethanol to obtain AgInS2 core quantum dots.
[0051] 3) The zinc-sulfur precursor mixture (0.6 mmol of zinc stearate Zn(St)2 and 0.3 mmol of sulfur powder were dissolved in 2 mL of trioctyl phosphate (TOP) and 2 mL of octadecene (ODE) at 120 °C) was injected into the flask containing the above AgInS2 core quantum dots. Subsequently, the reaction temperature was rapidly raised to 170 °C and maintained for 1 hour to form a ZnS shell. Then, the same amount of zinc-sulfur precursor mixture was injected again, and the temperature was raised to 210 °C and maintained for 1 hour to further grow the ZnS shell. The obtained quantum dots were purified three times using n-hexane and ethanol, and the purified quantum dots were stored as an n-hexane solution for characterization. Some of the purified quantum dots were vacuum dried into a powder.
[0052] Example 7
[0053] 1) 0.08 mmol of silver nitrate (AgNO3), 0.4 mmol of indium chloride hydrate (InCl3·4H2O), 0.6 mmol of oleic acid (OA), 2 mmol of dodecanethiol (DDT), and 15 mL of octadecene (1-ODE) were mixed in a 50 mL three-necked flask. The mixture was heated to 80 °C and vacuum was applied for 30 minutes. Then, the temperature was raised to 130 °C under a nitrogen atmosphere to completely dissolve AgNO3.
[0054] 2) Subsequently, the temperature was lowered to 110 °C, and vacuum was applied for 2 hours, followed by nitrogen filling. The sulfur precursor (0.3 mmol of sulfur powder dissolved in 4 mL of oleylamine at 120 °C) was rapidly injected into the above mixture for reaction, and the reaction was maintained at 110 °C for 20 minutes to promote the growth of AgInS2 core quantum dots. The obtained AgInS2 quantum dots were purified three times using n-hexane and ethanol to obtain AgInS2 core quantum dots.
[0055] 3) Inject the zinc sulfide precursor mixture (dissolve 0.6 mmol of zinc stearate Zn(St)2 and 0.3 mmol of sulfur powder in 2 mL of trioctyl phosphate (TOP) and 2 mL of octadecene (ODE) at 120 °C) into the flask containing the above AgInS2 core quantum dots. Subsequently, quickly raise the reaction temperature to 180 °C and maintain it for 1 hour to form the ZnS shell. Then, inject the same amount of zinc sulfide precursor mixture again, and raise the temperature to 220 °C and maintain it for 1 hour to further grow the ZnS shell. The obtained quantum dots are purified three times using n-hexane and ethanol, and the purified quantum dots are stored in the form of n-hexane solution for characterization. Some of the purified quantum dots are vacuum dried into powder.
[0056] Comparative Example 1
[0057] Synthesis of AgInS2:Zn / ZnS quantum dots: Use the AgInS2 core quantum dots prepared in Example 1.
[0058] 1) At 110 °C, quickly inject 0.6 mmol of zinc precursor (dissolve 0.6 mmol of Zn(St)2 in 2 ml of TOP and 2 ml of ODE at 100 °C) into the reaction flask containing AgInS2 core quantum dots without any purification. Quickly raise the reaction temperature to 180 °C to obtain AgZnS2:Zn quantum dots.
[0059] 2) During the growth of AgInS2:Zn quantum dots, samples are taken regularly to monitor the spectral changes. When the monitored spectral wavelength reaches the green region (about 520 nm), inject the zinc sulfide mixed precursor (dissolve 0.6 mmol of zinc stearate Zn(St)2 and 0.3 mmol of sulfur powder in 2 mL of TOP and 2 mL of ODE at 120 °C) into the above reactants. Then, quickly raise the temperature to 210 °C and maintain it for 1 hour to promote the epitaxial growth of the ZnS shell. The obtained AgInS2:Zn / ZnS quantum dots are purified three times using n-hexane and ethanol, and then redispersed in n-hexane for subsequent characterization. Some of the purified quantum dots are vacuum dried into powder, which are the green-emitting AgInS2:Zn / ZnS quantum dots.
[0060] The present invention first synthesized a series of AgInS2 quantum dots with different emission wavelengths by adjusting the silver / indium ratio. As Figure 1As shown in a, with the increase of indium content, the photoluminescence (PL) peak of AgInS2 quantum dots shows a blue shift. When the silver / indium ratio reaches 1:20, the PL peak stabilizes at about 600 nm. During the synthesis of AgInS2 core quantum dots, the difference in reactivity between silver and indium when binding to sulfur generates various defects, which in turn affect their luminescence properties. The absorption spectrum follows a similar trend, also showing a blue shift with the increase of indium content. This blue shift is attributed to the enlarged quantum dot bandgap with the increase of indium content. By adjusting the silver / indium ratio from 1:20 to 1:1, the emission spectrum of AgInS2 quantum dots can be continuously adjusted between 600 nm and 795 nm. The optimized AgInS2 core quantum dots exhibit a low PL QY (<25%), a large Stokes shift (>100 nm), and a wide PL peak width (130 - 190 nm). This broadband emission of AgInS2 nanocrystals is mainly attributed to defect-related emission, originating from the donor-acceptor pair (DAP) recombination related to surface defects.
[0061] Figure 2 Figure shows the fluorescence property diagrams of the quantum dots prepared in Comparative Example 1 and Example 1 under varying reaction times. The figure shows that the absorption and emission spectra of AgInS2-based quantum dots exhibit a blue shift over time, and this blue shift trend is closely related to the reaction duration. Specifically, in Comparative Example 1, the emission wavelength of AgInS2:Zn quantum dots moves from the initial 624 nm (AgInS2 core) to 526 nm within 20 minutes after the first addition of the zinc precursor only. With the coating of the ZnS shell, the emission wavelength of AgInS2:Zn / ZnS quantum dots further moves to 524 nm. The full width at half maximum (FWHM) of the quantum dots gradually decreases throughout the process (as shown in Figure 2 Figures 2a and 2c). However, due to the exchange of Zn²⁺ and the coating of the ZnS shell, the PLQY of AgInS2:Zn / ZnS quantum dots decreases compared to that of AgInS2 core quantum dots. In contrast, in Example 1, after adding the mixed ZnS precursor, the emission wavelength of AgInS2 / ZnS quantum dots moves to 524 nm only after 120 minutes of reaction. The FWHM of the quantum dots decreases, and finally the green-emitting AgInS2 / ZnS quantum dots exhibit a PL QY as high as 60%.
[0062] Figure 3TEM images of (a) AgInS2 core, (b) AgInS2:Zn, (c) AgInS2:Zn / ZnS, and (d) AgInS2 / ZnS quantum dots. The inset is a particle size distribution histogram. The initial AgInS2 core quantum dot diameter is about 2.2 nm. After zinc ion exchange, the size of the AgInS2:Zn quantum dots (Comparative Example 1) increased to about 2.32 nm, while with the coating of the ZnS shell, the size of the AgInS2:Zn / ZnS quantum dots reached 3.3 nm. In contrast, the diameter of the AgInS2 / ZnS quantum dots (Example 1) is 4.4 nm and has more obvious and ordered lattice fringes ( Figure 3 ). Therefore, we speculate that the decrease rather than increase of the PL QY of AgInS2:Zn / ZnS QDs may be due to the too-fast exchange of zinc ions into the AgInS2 core, thereby introducing irreversible internal lattice defects and reducing its luminescence efficiency.
[0063] Application Examples
[0064] The dried quantum dot powders prepared in the above examples and comparative examples were uniformly mixed with UV-curable adhesives to prepare quantum dot mixtures with a concentration of 2 mg / mL. Then, four different quantum dot mixtures with emission wavelengths of 524 nm, 564 nm, 599 nm and 632 nm were mixed in a specified volume ratio (4.9:0.7:0.8:9) and stirred for 3 hours under dark conditions to obtain the final device-level quantum dot slurry. The resulting device-level quantum dot slurry was dripped onto a 450 nm gallium nitride (GaN) LED chip and cured under 365 nm LED light for 10 minutes to obtain different white light emitting diodes.
[0065] Two white light emitting diodes (WLEDs) were fabricated to study the effect of green-emitting AgInS2-based quantum dots on the performance of WLED devices. In addition to green-emitting AgInS2:Zn / ZnS and AgInS2 / ZnS quantum dots, high-luminescence yellow, orange, and red AgInS2 / ZnS quantum dots (564, 599, and 632 nm) were synthesized. Figure 4 ).
[0066] The first WLED was obtained by mixing AgInS2 / ZnS quantum dots with wavelengths of 524, 564, 599 and 632 nm according to the above preparation method and volume ratio; The second WLED was obtained by replacing the 524-nm green-emitting AgInS2 / ZnS quantum dots used in the preparation of the first WLED with the AgInS2:Zn / ZnS quantum dots prepared in Comparative Example 1, and mixing them according to the above preparation method and volume ratio.
[0067] As Figure 5 shown in Fig. a, the green emission intensity of the first WLED is significantly stronger than that of the second WLED. This is because the PL QY of the green-emitting AgInS2:Zn / ZnS quantum dots is much lower than that of the green-emitting AgInS2 / ZnS quantum dots. The enhancement of green emission significantly improves the color rendering performance of the WLED. Specifically, the CRI Ra increases from the initial 92.3 to a record 97.1, the special CRI R9 increases significantly, from 80.8 to 90.2, and R13 increases from 96.3 to 99.2 ( Figure 5 Fig. b). The first AgInS2 / ZnS WLED exhibits bright and warm white (correlated color temperature CCT = 3681 K), with excellent color quality (CRI Ra = 97.1, R9 = 90.2, and R13 = 99.2), and at the same time, the maximum luminous efficacy (LE) is 81 lm / W, exceeding that of existing high-quality quantum dot-based WLEDs. In addition, as Figure 5 shown in Figs. c and 5d, due to the enhanced luminous efficiency of the green-emitting AgInS2 / ZnS quantum dots, the first WLED achieves better color and efficiency stability under different currents ( Figure 6 ).
[0068] As can be seen from the above embodiments, the present invention provides an AgInS2 / ZnS quantum dot with high fluorescence emission efficiency, a preparation method thereof, and an application thereof in a white light emitting diode. The research of the present invention finds that zinc ion exchange can effectively make the AgInS2 quantum dot emit green light. However, the rapid zinc ion exchange introduces irreversible lattice defects in the AgInS2 core quantum dot, thus generating a rapid non-radiative channel and significantly reducing the luminescence efficiency of the quantum dot. The AgInS2 / ZnS quantum dot prepared by the optimized scheme of the present invention exhibits a PL QY of up to 60% at 524 nm. In addition, we also fabricated a white light emitting diode (WLED) by combining AgInS2-based quantum dots of four colors (524, 564, 599, and 632 nm) with a 450 nm gallium nitride chip. The best WLED based on the AgInS2 / ZnS quantum dot produces bright and warm white light (CCT = 3682 K), with excellent color quality (CRI = 97.1, R9 = 90.2, R13 = 99.2), and a maximum luminous efficacy of 81 lm / W, which is superior to other existing quantum dot-based WLEDs. The research of the present invention may provide a potential strategy for other I-III-VI semiconductor nanocrystals in regulating the emission wavelength and enhancing the luminescence efficiency.
[0069] The above description is only a preferred embodiment of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing AgInS2 / ZnS quantum dots with high fluorescence luminescence efficiency, characterized in that: The following steps are involved: 1) silver nitrate, indium chloride, oleic acid, dodecanethiol and octadecene are mixed and reacted, and a mixture is obtained after heating; 2) Rapidly add the sulfur precursor to the mixture and react at a certain temperature to obtain AgInS2 core quantum dots; 3) Adding the zinc-sulfur precursor mixture to the AgInS2 core quantum dots for reaction to form a ZnS shell; then adding the same amount of the zinc-sulfur precursor mixture again for a secondary reaction to obtain AgInS2 / ZnS quantum dots with high fluorescence efficiency.
2. The method for preparing AgInS2 / ZnS quantum dots with high fluorescence efficiency according to claim 1, characterized in that: The molar ratio of silver nitrate to indium chloride is 0.02-0.4:0.4; The usage ratio of the silver nitrate, oleic acid, dodecanethiol and octadecene is 0.02-0.4 mmol: 0.5-0.8 mmol: 2-4 mmol: 5-15 mL.
3. The method for preparing AgInS2 / ZnS quantum dots with high fluorescence luminescence efficiency according to claim 1 or 2, characterized in that: In the step 1), the reaction temperature is 80-90°C, the reaction time is 20-30 minutes, and the heating temperature is 120-140°C.
4. The method for preparing AgInS2 / ZnS quantum dots with high fluorescence luminescence efficiency according to claim 1, characterized in that: The sulfur precursor is prepared by dissolving sulfur powder in oleylamine, and the usage ratio of the sulfur powder to oleylamine is 0.2-0.4 mmol:4 mL.
5. The method for preparing AgInS2 / ZnS quantum dots with high fluorescence luminescence efficiency according to claim 2 or 4, characterized in that: In the step 2), the reaction temperature is 100-120° C., and the reaction time is 10-20 min.
6. The method for preparing AgInS2 / ZnS quantum dots with high fluorescence luminescence efficiency according to claim 5, characterized in that: The zinc-sulfur precursor mixture is obtained by dissolving zinc stearate and sulfur powder in a mixed solvent of trioctyl phosphate and octadecene, and the dosage ratio of the zinc stearate, sulfur powder, trioctyl phosphate and octadecene is 0.4-0.8 mmol: 0.3 mmol: 2 mL: 2 mL.
7. The method for preparing AgInS2 / ZnS quantum dots with high fluorescence luminescence efficiency according to claim 1 or 6, characterized in that: In the step 3), the reaction temperature is 170-190° C., and the reaction time is 0.5-2 h.
8. The method for preparing AgInS2 / ZnS quantum dots with high fluorescence luminescence efficiency according to claim 1, characterized in that: In the step 3), the temperature of the secondary reaction is 200-220° C., and the time of the secondary reaction is 0.5-2 h.
9. AgInS2 / ZnS quantum dots with high fluorescence efficiency prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the AgInS2 / ZnS quantum dots with high fluorescence luminescence efficiency as claimed in claim 9 in white light emitting diodes.